Research progress on innate lymphoid cells 3 in skin wound healing - Wei ZHANG; Qianru HANG; Tengjiao XU; Yuge WENG; Yan DING (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
The skin wound healing is a complex physiological process involving coagulation, inflammation, proliferation, and remodeling. Innate immune cells play a crucial role in regulating signaling factors during skin wound healing. Due to their unique tissue distribution and origin, innate lymphoid cells 3 (ILC3), a member of innate immune cells, have the potential to regulate the wound healing process. They can secrete multiple cytokines, such as IL-17, IL-22, and GM-CSF, to maintain skin homeostasis, promote keratinocyte proliferation and epithelial cell migration, and participate in wound tissue reconstruction. The function of ILC3 is regulated by various signaling pathways, including RA-RAR, FFAR2, vitamin D receptor, DR3, and AhR, making them potential integrators of microenvironment around the wound. Numerous studies suggest the importance of ILC3 in skin wound healing, making them a potential therapeutic target in wound healing. This article comprehensively reviews the origin, tissue distribution, function, and signaling receptors of ILC3 and summarizes recent advances in the study of ILC3 in skin wound healing.